2014
DOI: 10.1128/mbio.01402-14
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP1 Is Important for Activation of Caspase-1 in Macrophages and Is Targeted by Yersinia pestis Type III Effector YopM

Abstract: YopM is a leucine-rich repeat (LRR)-containing effector in several Yersinia species, including Yersinia pestis and Y. pseudotuberculosis. Different Yersinia strains encode distinct YopM isoforms with variable numbers of LRRs but conserved C-terminal tails. A 15-LRR isoform in Y. pseudotuberculosis YPIII was recently shown to bind and inhibit caspase-1 via a YLTD motif in LRR 10, and attenuation of YopM− YPIII was reversed in mice lacking caspase-1, indicating that caspase-1 inhibition is a major virulence func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
70
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 60 publications
(75 citation statements)
references
References 41 publications
(74 reference statements)
2
70
0
Order By: Relevance
“…Although it is unclear which mechanisms YopM uses for inhibition of inflammasome activation, direct interaction with caspase-1 and the scaffold protein Iqgap1 have been proposed (15,16). Interactions between YopM and kinases such as RSK1/2 and PKN1/2 (55-57), known for binding to the effector, may also play a role in caspase-1 regulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it is unclear which mechanisms YopM uses for inhibition of inflammasome activation, direct interaction with caspase-1 and the scaffold protein Iqgap1 have been proposed (15,16). Interactions between YopM and kinases such as RSK1/2 and PKN1/2 (55-57), known for binding to the effector, may also play a role in caspase-1 regulation.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that YopM inhibits caspase-1 (15,16). Caspase-1 mediates maturation of IL-1␤ and IL-18, cytokines that promote a robust early immune response that enhances host resistance against Y. pestis infection (17,18).…”
mentioning
confidence: 99%
“…The activity of the T3SS itself, as well as the activity of translocated effectors, triggers inflammasome activation, which promotes Yersinia clearance in vivo (36,80). However, Yersinia also inhibits inflammasome activation through the activities of YopK and YopM (36,38,39). Recent studies have revealed that YopJ can cooperate with YopM in activated macrophages to limit inflammasome activation (78,81), although YopJ blockade of NF-B and MAPK signaling triggers the activation of caspase-8 and caspase-1 in naive macrophages (82,83).…”
Section: Discussionmentioning
confidence: 99%
“…YopM interferes with YopE-and YopT-mediated activation of the pyrin inflammasome by binding to protein kinase C-related kinases (PRKs) and promoting PRK-dependent phosphorylation and inactivation of pyrin (37). Interestingly, Yersinia pseudotuberculosis and Yersinia pestis YopK mutants are unable to prevent inflammasome activation despite the presence of YopM, indicating that YopM and YopK block the inflammasome via distinct, nonredundant mechanisms (36,38,40).…”
mentioning
confidence: 99%
See 1 more Smart Citation